Eksplorasi Perilaku Pemilih Muda Pada Pemilihan Walikota Dan Wakil Walikota Surakarta Tahun 2015 Melalui Pendekatan Konsep Trust And Distrust - Baruno, Suryo; , Prof. Dr. Bambang Setiaji; , Ihwan Susila, SE., M.Si., Ph.D (2017)
Young people are generally very cynical about politicians but are still interested in electoral process. This study explored the components of political trust from young voters' perpective and how it could affect their voting behaviour. Using grounded theory approach, data were collected through in-depth interviews to young voters in Surakarta. This study identifies the components of trust from young voters' perspective and shows how these have an impact to their decisions. This reseach could be useful for political candidates and policy maker to encourage young voters in the electoral process.